NUTRITIONAL APPLICATION AFFECTING RESISTANCE TO PHYTOPHTHORA PARASITlCA VAR. PIPERINA - NEMA, A. G. (Indian Phytopathology, 2002)
In attempts to manipulation of resistance with crop nutrients, nitrogen was found to increase the disease susceptibility, while phosphorus and potash reduced it. Potash was also found to increase the keeping quality of betel leaves.